Analisis Pemeriksaan Mean Arterial Pressure (MAP), Roll Over Test (ROT), Body Mass Indeks (BMI) Sebagai Skrining Pre-Eklampsia pada Kehamilan: Analysis of Examining Mean Arterial Pressure (MAP), Roll Over Test (ROT), Body Mass Index (BMI) as Pre-Eclampsian Screening in Pregnancy - Ningrum, Nining Mustika (Stikes Wira Medika Bali, 2020)
Pre-eclampsia is an abnormality that can harm both the mother and the fetus, therefore every pregnant woman must be screened to detect pre-eclampsia symptoms. The purpose of this study was to analyze the effect of checking Mean Arterial Pressure (MAP), Roll Over Test (ROT), Body Mass Index (BMI) as a screening for pre-eclampsia in pregnancy. This type of research is quantitative analytic using a Quasi-experimental research design in the Midwives Practice Mandiri working area of Puskesmas Pulorejo, Jombang Regency. Sample: 48 pregnant women in Trimester II who met the inclusion criteria were using purposive sampling technique. The instruments used were the KIA book, checklist. Chi-square statistical test and logistic regression test. The results of the bivariate test using Chi-Square found that pregnant women with positive MAP had a greater risk of developing pre-eclampsia, mothers who had positive ROT had 2 times the risk of developing pre-eclampsia compared to negative ROTs, mothers who were overweight or obese based on BMI had a risk more likely to have pre-eclampsia. The results of the multivariate analysis carried out with logistic regression tests together showed the effect of MAP, ROT and BMI examinations as a screening for pre-eclampsia in pregnancy. It is hoped that midwives and service providers for pregnant women to carry out MAP, ROT and control weight gain in pregnant women based on the Body Mass Index to screen for pre-eclampsia in pregnancy